2018
DOI: 10.1002/jhet.3225
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review on the Synthesis and Reactions of Pyrazolopyrazine Heterocycles

Abstract: The pyrazolopyrazine ring system is a very interesting class of heterocyclic compounds that were considered as important scaffolds of many efficacious biologically active agents that show anticancer with low toxicity, antioxidant, anticonvulsant, antiparasitic, anti‐inflammatory, antiviral, antibacterial, antifungal, and analgesic activities. This review throws light on the detailed synthetic approaches for the synthesis and reactions of pyrazolopyrazine moiety. This follow up may encourage the chemists to gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 75 publications
(83 reference statements)
1
10
0
Order By: Relevance
“…Among the N -heterocycle compounds, pyrazolo[3,4- b ] pyridine scaffold is the valuable scaffold of material drugs and KDR kinase inhibition 53 , 54 . Recent research in material chemistry confirmed that pyrazolo[3,4- b ] pyridine compounds are key intermediates in industry, semiconductors and organic light-emitting diodes 55 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the N -heterocycle compounds, pyrazolo[3,4- b ] pyridine scaffold is the valuable scaffold of material drugs and KDR kinase inhibition 53 , 54 . Recent research in material chemistry confirmed that pyrazolo[3,4- b ] pyridine compounds are key intermediates in industry, semiconductors and organic light-emitting diodes 55 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Hoffmann-La Roche directed to effective Bruton's Tyrosine Kinase inhibition the corresponding lead compound (1 f) bearing amine substituent was identified and scaled up for toxicology studies. [7h] The approaches to the synthesis of pyrazolo [1,5-a]pyrazine heterocyclic system (2) were recently reviewed [8] and the main techniques used by medicinal chemists are summarized in Figure 2. Important, that all approaches were based on the annelation of the pyrazine ring to the pyrazole one.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches to the synthesis of pyrazolo[1,5‐a]pyrazine heterocyclic system ( 2 ) were recently reviewed [8] and the main techniques used by medicinal chemists are summarized in Figure 2. Important, that all approaches were based on the annelation of the pyrazine ring to the pyrazole one.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our previous work and because of increased interest in pyrazolo[3,4‐ b ]pyrazine moiety, some novel thienopyrazolopyrazines that have not been reported previously were required for the study of antimicrobial and anti‐inflammatory activities.…”
Section: Introductionmentioning
confidence: 99%